Revised understanding of iatrogenic lumbosacral nerve bowstringing disease: a case report and literature review - Gao, Haoran; Tian, Lei; Tong, Yunyan; Zhang, Haibo; Zhang, Heling (Frontiers in Surgery, 2025)
BackgroundIatrogenic lumbosacral nerve bowstringing disease (ILNBD) is a severe complication of spinal surgery. The clinical presentation is often insidious and may be misdiagnosed as nerve root compression. Heightened diagnostic vigilance supported by characteristic radiological findings is essential.Case presentationThis case report a 63-year-old woman who underwent L3–L5 interbody fusion and internal fixation surgery for vertebral slippage combined with lumbar spinal stenosis. Her symptoms improved significantly on the second day after surgery, but she suddenly developed lower limb neurological dysfunction on the fifth day after surgery. Imaging studies showed that the internal fixation and interbody fusion devices were well positioned, with increased spinal canal volume and no space-occupying lesions. However, axial MRI revealed high tension of the cauda equina and positive nerve descent signs, consistent with the characteristics of bowstring disease.ConclusionExcessive expansion of the intervertebral space can lead to sustained static traction on the nerve roots. The appropriate fusion device height should be determined through a stepwise expansion test to avoid increased axial tension on the nerves. Additionally, technical operational details can independently induce bowstring syndrome, and stepwise tension assessment is crucial for preventing traction-related nerve damage.